Fiscal episodes and market power - Afonso, António (2022)
We assess the effect of fiscal episodes, as determined via alternative approaches, on GDP and on markups in a panel of 14 OECD countries. Our results with narrative action-based data show counter-cyclicality since negative fiscal shocks increase markups. Additional empirical exercises reveal that spending-based consolidation programs have a more counter-cyclical effect on the behaviour of markups over the short and medium term than tax-based ones. Moreover, in times of economic contraction the degree of counter-cyclicality of negative (positive) government spending (tax) shocks is larger than during economic expansions.